Evaluation of Fingerstick Cryptococcal Antigen Lateral Flow Assay in HIV-Infected Persons : A Diagnostic Accuracy Study - Williams, Darlisha A.; Kiiza, Tadeo; Kwizera, Richard; Kiggundu, Reuben; Velamakanni, Sruti; Meya, David B.; Rhein, Joshua; Boulware, David R. (Clinical Infectious Diseases, 2015)
Cryptococcus neoformans is the most common cause of adult meningitis in sub-Saharan Africa. The cryptococcal antigen (CRAG) lateral flow assay (LFA) has simplified diagnosis as a point-of-care test approved for serum or cerebrospinal fluid (CSF). We evaluated the accuracy of the CRAG LFA using fingerstick whole blood compared with serum/plasma and CSF for diagnosing meningitis. Methods. From August 2013 to August 2014, CRAG LFA (IMMY, Norman, Oklahoma) tests were performed on fingerstick whole blood, plasma/serum, and CSF in 207 HIV-infected adults with suspected meningitis in Kampala, Uganda. Venous blood was also collected and centrifuged to obtain serum and/or plasma. CSF was tested after lumbar puncture. Results. Of 207 participants, 149 (72%) had fingerstick CRAG-positive results. There was 100% agreement between fingerstick whole blood and serum/plasma. Of the 149 fingerstick CRAG-positive participants, 138 (93%) had evidence of cryptococcal meningitis with a positive CSF CRAG. Eleven participants (5%) had isolated cryptococcal antigenemia with a negative CSF CRAG and culture, of whom 8 had CSF abnormalities (n = 3 lymphocytic pleocytosis, n = 5 elevated protein, n = 4 increased opening pressure). No persons with cryptococcal meningitis had negative fingersticks. Conclusions. The 100% agreement between whole blood, serum, and plasma CRAG LFA results demonstrates that fingerstick CRAG is a reliable bedside diagnostic test. Using point-of-care CRAG testing simplifies screening large numbers of patients and enables physicians to prioritize on whom to measure CSF opening pressure using manometers.